Ionized Air as a Process Medium for Machining - Vasilko, Karol; Matija, Rudolf (Manufacturing Technology Journal, 2019)
The application of cutting liquids in the machining of the pertsgreatly affects the working environment. Descpite the efforts to prolong life, chemical aliminaion of bacteria formation, development of new liquid configurations, their negative influence on production (health hazard to the operator, corrosion of workpieces, need of recycling or disposal), it outweighs the benefits (decrease of cutting forces, cutting temperature reduction).The good is a gaseous environment. The current gaseous environments show the current application of ionized air. In the article are experimental results when applying this media during machining.
Keywords: machining; lubricants; cooling; ionozed air